¿Por qué la medicina le interesa al escepticismo? - Miroli, Alejandro G. (ARFIL y UNL, 2018)
This paper studies the relationship between Pyrrhonian skepticism and medicine in the contemporary scenario and tries to offer a characterization of contemporary skepticism and of present day medical schools. We propose (i) that there is a kind of knowledge that corresponds to the notion of an experience purified by epokhé which is the narrative knowledge, (ii) that Narrative Based Medicine (MBN) is the medical school that can be linked to the neopyrrhonian project and (iii) that MBN is a leading case for analyzing the criteriological role of narrative knowledge.